COVID-19 in Bangladesh: Impacts on Production, Poverty and Food Systems - Dorosh, Paul; Pradesha, Angga; Raihan, Selim; Thurlow, James (2020)
By Paul Dorosh, Angga Pradesha, Selim Raihan, and James Thurlow